To Know them, Remove their Information: An Outer Methodological Approach to Biophysics and Humanities. - Tozzi, Arturo (Philosophia, 2023)
Set theory faces two difficulties: formal definitions of sets/subsets are incapable of assessing biophysical issues; formal axiomatic systems are complete/inconsistent or incomplete/consistent. To overtake these problems reminiscent of the old-fashioned principle of individuation, we provide formal treatment/validation/operationalization of a methodological weapon termed "outer approach" (OA). The observer's attention shifts from the system under evaluation to its surroundings, so that objects are investigated from outside. Subsets become just "holes" devoid of information inside larger sets. Sets are no longer passive containers, rather active structures enabling their content's examination. Consequences/applications of OA include: a) operationalization of paraconsistent logics, anticipated by unexpected forerunners, in terms of advanced truth theories of natural language; b) assessment of embryonic craniocaudal migration in terms of Turing's spots; c) evaluation of hominids' social behaviors in terms of evolutionary modifications of facial expression's musculature; d) treatment of cortical action potentials in terms of collective movements of extracellular currents, leaving apart what happens inside the neurons; e) a critique of Shannon's information in terms of the Arabic thinkers' active/potential intellects. Also, OA provides an outer view of a) humanistic issues such as the enigmatic Celestino of Verona's letter, Dante Alighieri's "Hell" and the puzzling Voynich manuscript; b) historical issues such as Aldo Moro's death. Summarizing, we suggest that the safest methodology to quantify phenomena is to remove them from our observation and tackle an outer view, since mathematical/logical issues such as selective information deletion and set complement rescue incompleteness/inconsistency of biophysical systems.